2015
DOI: 10.3917/rief.037.0115
|View full text |Cite
|
Sign up to set email alerts
|

Manger à la maison sous le poids des normes. Les négociations familiales autour de l’alimentation

Abstract: Cet article se propose d’explorer la configuration des logiques familiales autour des enjeux alimentaires. Les repas quotidiens sont le théâtre de négociations, d’un contrôle par les parents variable, plus ou moins intériorisé par les enfants, ou de stratégies et de tactiques utilisées par chacun en réponse aux normes nutritionnelles en vigueur et aux normes familiales. La méthodologie utilisée est ethnographique : 70 entretiens ont été menés dans les familles des élèves enquêtés après avoir passé un an à les … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…DeVault also reported that some working-class women shared the middle-class notion that meals should be occasions for family communications, but that these aspirations usually resulted in conflict during meals, as they would not necessarily correspond to the partner’s expectations of family meals [ 46 ]. There also exists social differentiation in the organisation of meals in families in France: while higher-class families value that all the family members eat the same food during the meals, leaving less room for negotiations with children, while children from lower classes have more agency in the choice of the food they eat [ 62 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DeVault also reported that some working-class women shared the middle-class notion that meals should be occasions for family communications, but that these aspirations usually resulted in conflict during meals, as they would not necessarily correspond to the partner’s expectations of family meals [ 46 ]. There also exists social differentiation in the organisation of meals in families in France: while higher-class families value that all the family members eat the same food during the meals, leaving less room for negotiations with children, while children from lower classes have more agency in the choice of the food they eat [ 62 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Family food practices, including the family meal, can also be a negotiation with children [ 76 ], who often contest and resist adult rules [ 83 , 111 ]. They influence family food purchases [ 112 ], and their preferences impact the entire family’s diet [ 113 , 114 ] and can constitute barriers to the implementation of parents’ ideals of a healthy diet [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…L'alimentation des enfants, depuis leur naissance, est surtout une affaire de femmes [Gojard, 2010]. Face à la large diffusion des injonctions à une alimentation saine, omniprésentes dans les médias, plusieurs travaux ont souligné la résistance des familles populaires, attachées à la liberté de manger et surtout de faire manger aux enfants les aliments qui leur plaisent [Régnier et Masullo, 2009 ;Maurice, 2015]. On ne retrouve pas une telle distance et résistance vis-à-vis des normes diététiques dans nos monographies de ménages : ces mères, dont certaines sont employées et d'autres ouvrières, sont « à l'écoute des recommandations nutritionnelles », tout comme les mères de classes supérieures décrites par Aurélie Maurice [2015].…”
Section: L'éducation Au Quotidienunclassified